基于改进结构理论下鼓式制动器振动噪声抑制方法研究 - 韩芸芳 (Jixie chuandong)
For the problem of drum brake noise and vibration during braking,through the drum brake frequency excitation force calculation process,the structure of the brake is improved.The finite element and experimental verification of the improve structure brake is carried out,thereby a improved method of drum brake noise and vibration suppression structure is obtained.The results show that the improve structure method of the drum brakes can be improved significantly inhibit brake noise and vibration phenomena,structural improvement previous drum brake shoes and the floor under the excitation force components prone resonance phenomenon,and the improved model structure in the vicinity of the exciting force size and no resonance point,by the improved drum brake test,the test results and simulation results is highly correlated.